Catalyst for preparing acrylonitrile through propylene ammoxidation as well as preparation method and application of catalyst

By optimizing the composite oxide components and preparation process of Fe, Mo, and Bi elements in the catalyst, controlling the amount of Lewis acid, the problem of poor activity of the catalyst under high load conditions is solved, and high acrylonitrile yield and stability are achieved , improves productivity and economicality.

CN119215915AActive Publication Date: 2024-12-31CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310776465.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-28
Publication Date
2024-12-31
Estimated Expiration
2043-06-28

AI Technical Summary

Technical Problem

The existing acrylonitrile catalysts have poor activity under high load conditions, resulting in low yield and poor stability of acrylonitrile, which cannot meet the production needs under high load conditions.

Method used

Use composite oxides including three elements: Fe, Mo, Bi as active components, and optimize the components and preparation process of the catalyst to control the amount of strong Lewis acid within 60% of the total Lewis acid amount, and add appropriate A multi-dentate ligand complexing agent and a refractory oxide support are prepared by slurry cooking and colloid grinding and other steps to prepare a catalyst with high activity and selectivity.

Benefits of technology

Under high load conditions, the catalyst can maintain a high acrylonitrile single-pass yield for a long time, improving the efficiency and economy of acrylonitrile production. The propylene conversion rate can reach more than 99% and the one-pass yield can reach more than 84%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004309605850000131
    Figure BDA0004309605850000131
  • Figure BDA0004309605850000141
    Figure BDA0004309605850000141
Patent Text Reader

Abstract

The invention discloses a catalyst for preparing acrylonitrile through propylene ammoxidation as well as a preparation method and application of the catalyst. The catalyst provided by the invention comprises an active component and a carrier, wherein the acid amount of strong Lewis acid in the catalyst does not exceed 60% of the total Lewis acid amount. When the catalyst is used for a reaction for preparing acrylonitrile through propylene ammoxidation, the catalyst not only has higher propylene ammoxidation activity and acrylonitrile selectivity, but also has longer service life under a high-load condition, and can maintain higher single-pass yield of acrylonitrile for a long time, so that the efficiency and economical efficiency of acrylonitrile production are greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalysts, and in particular to a catalyst for preparing acrylonitrile by ammoxidation of propylene, and a preparation method and application thereof. Background Art

[0002] Acrylonitrile, as an important basic chemical raw material, is currently generally produced by fluidized bed ammoxidation process. Among them, the catalyst is one of the core technologies of the process, and its research and improvement have never stopped. Developing acrylonitrile synthesis catalysts that can be used for high catalyst loads, that is, increasing the number of tons of propylene that can be processed per ton of catalyst per hour, is an important trend in the development of acrylonitrile catalysts. However, with the increase of catalyst load, the feed amount of the reactor increases, the corresponding contact time between the catalyst and the raw material will also be shortened, and higher requirements are also placed on the redox performance of the catalyst itself. The existing catalysts cannot fully adapt to the requirements under high load conditions due to their own redox performance. When used under high load conditions, it is very easy to cause the problem of rapid reduction of acrylonitrile yield and poor stability.

[0003] The raw materials for the propylene ammoxidation reaction include propylene, ammonia and air. The catalyst needs to activate propylene and ammonia at the same time to achieve efficient reaction. Studies have shown that Mo-Bi catalysts have a strong ability to activate ammonia and can effectively activate ammonia at a relatively low temperature (above 380°C). The main rate-determining step of the reaction is the adsorption and activation of propylene. The adsorption and activation rate of propylene molecules on the catalyst surface has an important influence on the activity of the catalyst and the selectivity of the reaction. A better catalyst should have a faster propylene adsorption and desorption rate and a moderate propylene adsorption strength to ensure that the product is desorbed from the catalyst surface as quickly as possible, thereby reducing the production of by-products such as CO and CO2.

[0004] By controlling the spatial distribution of each element in the catalyst, or adding an appropriate carrier modifier, the performance of the catalyst can be improved to a certain extent. For example, CN111744493A discloses a kind of acrylonitrile catalyst, which can improve the stability of the catalyst in the long-term operation process by controlling the relative size of the Mo / Bi element molar ratio of the catalyst particle surface and the bulk Mo / Bi element molar ratio, but the load used during the catalyst evaluation is relatively low. CN107282063B, CN107282060B, CN107282065B and CN107282094B disclose that a certain amount of zirconium oxide, titanium oxide, diatomaceous earth, and ZSM-5 molecular sieve are added as carrier modifiers during the catalyst preparation process, which can improve the selectivity and stability of the catalyst in the propylene ammoxidation reaction, but its catalyst evaluation is also carried out under relatively low load conditions.

[0005] Therefore, the problems of low acrylonitrile yield and poor stability of propylene ammoxidation catalyst under high load conditions need to be solved urgently. Summary of the invention

[0006] In view of the problem that the catalyst for preparing acrylonitrile by propylene ammoxidation in the prior art has poor activity under high load conditions, the present invention provides a catalyst for preparing acrylonitrile by propylene ammoxidation and a preparation method and application thereof. The catalyst of the present invention is used in the propylene ammoxidation reaction, and has high propylene ammoxidation activity and acrylonitrile selectivity, and can maintain a high acrylonitrile single-pass yield for a long time under high load conditions.

[0007] The first aspect of the present invention provides a catalyst for preparing acrylonitrile by ammoxidation of propylene, the catalyst comprising an active component and a carrier, wherein the amount of strong Lewis acid in the catalyst does not exceed 60% of the total Lewis acid amount, preferably 30% to 60%.

[0008] In the above technical solution, the active component is a composite oxide, which includes at least oxides of three elements: Fe, Mo, and Bi. Preferably, its general formula is A a B b C c Fe d Bi e Mo f O x , wherein A is selected from alkali metal elements, preferably at least one of Li, Na, K, Rb and Cs; B is selected from at least one of Ca, Ba, Sr, Mn, Co, Ni, Zn, Mg, Al, Cr, Nb, Sb, Te and W; C is selected from at least one of rare earth elements, preferably at least one of La, Ce, Pr, Nd and Sm.

[0009] In the above technical solution, the value range of a is 0 to 3, the value range of b is 0 to 15, the value range of c is 0 to 5, the value range of d is 0.1 to 12, the value range of e is 0.01 to 5, the value range of f is 9 to 16, and x is the total number of oxygen atoms required to satisfy the valence of each element in the above active component.

[0010] In the above technical scheme, the value range of a is preferably 0.05 to 2.5, including but not limited to: 0.06, 0.10, 0.15, 0.20, 0.25, 0.30, 0.35, 0.40, 0.45, 0.50, 1.00, 1.50, 2.00, 2.05, 2.10, 2.15, 2.20, 2.25, 2.30, 2.40, 2.50.

[0011] In the above technical scheme, the value range of b is preferably 1 to 12.5, including but not limited to: 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0, 10.5, 11.0, 11.5, 12.0, 12.5.

[0012] In the above technical scheme, the value range of c is preferably 0.01 to 3, including but not limited to: 0.05, 0.10, 0.15, 0.20, 0.25, 0.30, 0.35, 0.40, 0.45, 0.50, 0.55, 0.60, 0.65, 0.70, 0.75, 0.80, 0.85, 0.90, 0.95, 1.00, 1.50, 2.00, 2.50, 3.00.

[0013] In the above technical solution, the value range of d is preferably 0.5 to 10, including but not limited to: 1.0, 2.0, 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, 9.0, 10.0.

[0014] In the above technical solution, the value range of e is preferably 0.01 to 3, including but not limited to: 0.05, 0.10, 0.15, 0.20, 0.25, 0.30, 0.35, 0.40, 0.45, 0.50, 1.00, 1.05, 1.10, 1.15, 1.20, 1.25, 1.30, 1.35, 1.40, 1.45, 1.50, 1.55, 1. 60, 1.65, 1.70, 1.75, 1.80, 1.85, 1.90, 1.95, 2.00, 2.05, 2.10, 2.15, 2.20, 2.25, 2.30, 2.35, 2.40, 2.45, 2.50, 2.55, 2.60, 2.65, 2.70, 2.75, 2.80, 2.85, 2.90, 2.95, 3.00.

[0015] In the above technical solution, the value range of f is preferably 10-15, including but not limited to: 10.0, 10.5, 11.0, 11.5, 12.0, 12.5, 13.0, 13.5, 14.0, 14.5, 15.0.

[0016] In the above technical solution, the atomic molar ratio of e / f is 0.005 to 0.35, preferably 0.01 to 0.25; the atomic molar ratio of d / f is 0.02 to 1.25, preferably 0.1 to 0.8.

[0017] In the above technical solution, the carrier is a refractory oxide, preferably at least one of silicon dioxide, zirconium dioxide and titanium dioxide, and more preferably silicon dioxide.

[0018] In the above technical solution, based on the weight of the catalyst, the content of the active component in terms of oxide is 30% to 80%, and the content of the carrier is 20% to 70%.

[0019] A second aspect of the present invention provides a method for preparing the above-mentioned catalyst for preparing acrylonitrile by ammoxidation of propylene, comprising the following steps:

[0020] (a) dissolving a Mo precursor to obtain a mixed solution I;

[0021] (b) dissolving an Fe precursor, a Bi precursor, an optional precursor of an A element, an optional precursor of an B element, and an optional precursor of an C element to obtain a mixed solution II;

[0022] (c) mixing the complexing agent with the mixed solution I obtained in step (a), the mixed solution II obtained in step (b), and the carrier precursor solution to obtain slurry I;

[0023] (d) boiling the slurry I obtained in step (c) to obtain slurry I';

[0024] (e) The slurry I' obtained in step (d) is transferred to a colloid mill for grinding, spray-drying and calcining to obtain the catalyst for preparing acrylonitrile by ammoxidation of propylene.

[0025] In the above technical scheme, the preparation method of the catalyst for preparing acrylonitrile by ammoxidation of propylene comprises the following steps:

[0026] (a) dissolving a Mo precursor to obtain a mixed solution I;

[0027] (b) dissolving an Fe precursor, a Bi precursor, a precursor of the A element, a precursor of the B element, and a precursor of the C element to obtain a mixed solution II;

[0028] (c) mixing the complexing agent with the mixed solution I obtained in step (a), the mixed solution II obtained in step (b), and the carrier precursor solution to obtain slurry I;

[0029] (d) boiling the slurry I obtained in step (c) to obtain slurry I';

[0030] (e) The slurry I' obtained in step (d) is transferred to a colloid mill for grinding, spray-drying and calcining to obtain the catalyst for preparing acrylonitrile by ammoxidation of propylene.

[0031] In the above technical solution, the molar ratio of the complexing agent contained in the slurry I described in step (c) to the total molar number of Fe, Bi and Mo contained in the active component precursor is 0.01-0.25:1.

[0032] In the above technical solution, in step (c), the complexing agent is a multidentate ligand, preferably any one of oxalic acid, citric acid, tartaric acid, ethylenediaminetetraacetic acid, ethylene glycol, and glycerol.

[0033] In the above technical scheme, in the mixed solution I described in step (a), there is no special requirement for the solvent used. Suitable solvents include any liquid used in the art for convenient mixing of raw materials (such as precursors) when synthesizing catalysts, more specifically including alcohol and water, especially C1-C6 monohydric alcohol and water, more preferably water.

[0034] In the above technical scheme, in the mixed solution II described in step (b), there is no special requirement for the solvent used. Suitable solvents include any liquid used in the art for convenient mixing of raw materials (such as precursors) when synthesizing catalysts, more specifically including alcohol and water, especially C1-C6 monohydric alcohol and water, more preferably water.

[0035] In the above technical solution, the precursors of the active components Mo, Bi, Fe, A, B, and C in the catalyst can be compounds commonly used in the art, and there is no special limitation in the present invention.

[0036] In the above technical solution, in step (c), the carrier precursor is a refractory oxide precursor, preferably at least one of silicon dioxide, zirconium dioxide, and titanium dioxide precursors, and more preferably silica sol. The solid content of the silica sol is 20 to 50 wt% in terms of silicon dioxide, and the average particle size is 5 to 40 nm. Preferably, the particle size distribution of the silica sol conforms to the normal distribution curve.

[0037] In the above technical solution, in step (d), the conditions for cooking the slurry include: a temperature of 10 to 80° C., a time of 0.1 to 12 h, and a stirring speed of 200 to 1000 rpm.

[0038] In the above technical solution, in step (e), the grinding conditions include: a rotation speed of 500 to 1500 rpm and a time of 0.5 to 1.5 h.

[0039] In the above technical solution, in step (e), the spray drying conditions include: the drying heat source is air, the drying temperature is 250-400°C, the drying time is 0.5-3h, and the average diameter of the spray droplets is 40-200μm.

[0040] In the above technical solution, in step (e), the calcination conditions include: in an oxygen-containing atmosphere (the volume fraction of oxygen is 10% to 50%), the calcination temperature is 200 to 750° C., and the calcination time is 2 to 8 hours.

[0041] A third aspect of the present invention provides a use of the above catalyst in the reaction of ammoxidation of propylene to produce acrylonitrile.

[0042] In the above technical scheme, there is no special limitation on the specifications of propylene, molecular oxygen and ammonia; although the content of low molecular weight saturated hydrocarbons in the raw material propylene has no effect on the reaction, from an economic point of view, the propylene concentration is preferably greater than 85% (mol); fertilizer-grade liquid ammonia can be used as ammonia; the molecular oxygen required for the reaction can be pure oxygen, oxygen-enriched oxygen and air from a technical point of view, but air is preferably used from economic and safety considerations.

[0043] In the above technical scheme, the reaction conditions of the propylene ammoxidation to acrylonitrile reaction include: the molar ratio of propylene: ammonia: air is 1: 1.0-1.5: 8-10.5, preferably 1: 1-1.3: 8.8-10. The reaction temperature is 400-470°C, preferably 410-450°C, the reaction pressure (gauge pressure) is 0.03-0.15MPa, preferably 0.06-0.14MPa, and the weight hourly space velocity is 0.045-0.15h -1 , preferably 0.06~0.12h -1 .

[0044] In the above technical solution, the reaction adopts a fluidized bed process, and the average particle size of the catalyst can be 40 to 60 microns.

[0045] Compared with the prior art, the present invention has the following advantages:

[0046] The acidity and alkalinity of the catalyst surface has a great influence on the selectivity of the catalyst and the adsorption behavior of the reactants. Too many strong Lewis acid sites in the catalyst will increase the number of cracking sites in the catalyst, increasing the selectivity of CO and CO2 in the catalyst; while weak Lewis acidity is not conducive to the adsorption of the reaction substrate on the catalyst, reducing the activity of the catalyst. The inventors have found through research that by optimizing the components of the catalyst, adding appropriate multidentate ligand complexing agents during the preparation process, and adding a colloidal mill grinding process during the preparation process to promote the uniform dispersion of the active components, the proportion of the strong Lewis acid content in the catalyst to the total Lewis acid content can be controlled within a certain range, which helps to improve the catalytic activity of the catalyst under high load conditions. When the proportion of strong Lewis acid in the prepared catalyst does not exceed 60% of the total Lewis acid content, the performance of the catalyst under high load conditions is better.

[0047] The catalyst provided by the present invention is applied to the reaction of preparing acrylonitrile by propylene ammoxidation, and has high propylene ammoxidation activity and acrylonitrile selectivity. At the same time, the catalyst has a long service life under high load conditions and can maintain a high acrylonitrile single-pass yield for a long time, thereby greatly improving the efficiency and economy of acrylonitrile production. The propylene conversion rate can reach up to more than 99%, and the acrylonitrile single-pass yield can reach up to more than 84%. DETAILED DESCRIPTION

[0048] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0049] The present invention will be further described below by way of examples, but these examples do not limit the scope of the present invention in any way.

[0050] In the context of the present invention, pyridine adsorption-desorption infrared spectroscopy is used to determine the "strong Lewis acid content" and "total Lewis acid content" in the catalyst. Here, the so-called "strong Lewis acid content" refers to the amount of Lewis acid sites that can adsorb pyridine at a desorption temperature of 400°C; "total Lewis acid content" refers to the amount of Lewis acid sites that can adsorb pyridine at a desorption temperature of 200°C. The pyridine adsorption-desorption infrared experiment was carried out using a Nicolet iS50 infrared spectrometer from Thermo Scientific. About 15 mg of the catalyst sample was pressed into a tablet and placed in a pyridine adsorption-desorption infrared reaction cell. First, the catalyst was heated to 400°C under high vacuum conditions (<10- 5 Pa) and heated to 400℃ for pretreatment for 2h, then gradually cooled to 200℃ and collected the bulk infrared spectra of the sample at 400 and 200℃. Then, pyridine was adsorbed and heated, and the infrared spectra of the sample after pyridine desorption at 200℃ and 400℃ were collected in turn. The adsorbed pyridine spectrum at the corresponding temperature was obtained by subtracting the spectrum with the bulk spectrum at the corresponding temperature. -1 The peak area of ​​the characteristic peak at corresponds to the Lewis acid content of the sample at the corresponding temperature.

[0051] In the present invention, the ratio of the strong Lewis acid content = the strong Lewis acid content / the total Lewis acid content × 100%.

[0052] The activity evaluation of the catalyst in the present invention is carried out in a fluidized bed reactor with an inner diameter of 38 mm. The catalyst loading is 400 g, the reaction temperature is 430°C, the molar ratio of raw materials propylene: ammonia: air is 1:1.25:9.7, the reaction pressure (gauge pressure) is 0.085 MPa, and the reaction weight hourly space velocity (WWH) is 0.095 h -1 .

[0053] The conversion rate of propylene, selectivity of acrylonitrile and single-pass yield are used as indicators for evaluating catalyst performance, and their definitions are as follows:

[0054] Propylene conversion (%) = (moles of propylene consumed in the reaction / moles of propylene fed) × 100%;

[0055] Acrylonitrile selectivity (%) = (moles of acrylonitrile produced / moles of propylene consumed in the reaction) × 100%;

[0056] Acrylonitrile single-pass yield (%) = (number of moles of acrylonitrile produced / number of moles of propylene fed) × 100%.

[0057] Example 1 (normal recipe)

[0058] 753.5 g (NH4)6Mo7O 24 ·4H2O was dissolved in 250mL of water to obtain a mixed solution I. 228.3g of Bi(NO3)3·5H2O, 456.3g of Ni(NO3)2·6H2O, 137.0g of Co(NO3)2·6H2O, 380.3g of Fe(NO3)3·9H2O, 80.5g of Mg(NO3)2·6H2O, 4.4g of KOH, and 81.9g of Pr(NO3)3·6H2O were dissolved in 100mL of water to obtain a mixed solution II. Then, the mixed solution I, the mixed solution II and 2500g of silica sol with a weight concentration of 40wt% were mixed, and 51.1g of oxalic acid was added thereto to obtain a slurry I. Then, the slurry was boiled at 65°C and 300 rpm for 1.5 hours, and then the slurry was transferred to a colloid mill and ground at 750 rpm for 0.5 hours, and then spray-dried at 325°C for 1 hour, with an average diameter of 120 μm, to obtain particles. Finally, the obtained particles were calcined at 600°C for 4 hours in an oxygen-containing atmosphere (oxygen volume fraction 21%) to obtain a catalyst.

[0059] The composition of the catalyst obtained according to the above steps is expressed as follows:

[0060] 50%K 0.25 Co 1.5 Ni 5.0 Mg 1.0 Pr0.6 Fe 3.0 Bi 1.5 Mo 13.6 O x +50%SiO2

[0061] The amount of strong Lewis acid in the catalyst accounts for 55% of the total Lewis acid.

[0062] The activity evaluation of the catalyst showed that the propylene conversion rate of the catalyst was 99.2%, the acrylonitrile selectivity was 85.4%, and the acrylonitrile single-pass yield was 84.7%.

[0063] Example 2 (Bi / Mo, Fe / Mo ratio changes)

[0064] 782.5 g (NH4)6Mo7O 24 ·4H2O was dissolved in 250mL of water to obtain a mixed solution I. 197.6g of Bi(NO3)3·5H2O, 473.9g of Ni(NO3)2·6H2O, 142.3g of Co(NO3)2·6H2O, 296.2g of Fe(NO3)3·9H2O, 83.6g of Mg(NO3)2·6H2O, 4.6g of KOH, and 85.1g of Pr(NO3)3·6H2O were dissolved in 100mL of water to obtain a mixed solution II. Then, the mixed solution I, the mixed solution II and 2500g of silica sol with a weight concentration of 40wt% were mixed, and 50.2g of oxalic acid was added thereto to obtain a slurry I. Then, the slurry was boiled at 65°C and 300 rpm for 1.5 hours, and then the slurry was transferred to a colloid mill and ground at 750 rpm for 0.5 hours, and then spray-dried at 325°C for 1 hour, with an average diameter of 120 μm, to obtain particles. Finally, the obtained particles were calcined at 600°C for 4 hours in an oxygen-containing atmosphere (oxygen volume fraction 21%) to obtain a catalyst.

[0065] The composition of the catalyst obtained according to the above steps is expressed as follows:

[0066] 50%K 0.25 Co 1.5 Ni 5.0 Mg 1.0 Pr 0.6 Fe 2.25 Bi 1.25 Mo 13.6 O x +50%SiO2

[0067] The amount of strong Lewis acid in the catalyst accounts for 53% of the total Lewis acid.

[0068] The activity evaluation of the catalyst showed that the propylene conversion rate of the catalyst was 99.0%, the acrylonitrile selectivity was 85.1%, and the acrylonitrile single-pass yield was 84.2%.

[0069] Example 3 (Compared with Example 1, the ratio of the types of complexing agents added is changed)

[0070] 753.5 g (NH4)6Mo7O 24 ·4H2O was dissolved in 250mL of water to obtain a mixed solution I. 228.3g of Bi(NO3)3·5H2O, 456.3g of Ni(NO3)2·6H2O, 137.0g of Co(NO3)2·6H2O, 380.3g of Fe(NO3)3·9H2O, 80.5g of Mg(NO3)2·6H2O, 4.4g of KOH, and 81.9g of Pr(NO3)3·6H2O were dissolved in 100mL of water to obtain a mixed solution II. Then, the mixed solution I, the mixed solution II and 2500g of silica sol with a weight concentration of 40wt% were mixed, and 109.1g of citric acid was added thereto to obtain a slurry I. Then, the slurry was boiled at 65°C and 300 rpm for 1.5 hours, and then the slurry was transferred to a colloid mill and ground at 750 rpm for 0.5 hours, and then spray-dried at 325°C for 1 hour, with an average diameter of 120 μm, to obtain particles. Finally, the obtained particles were calcined at 600°C for 4 hours in an oxygen-containing atmosphere (oxygen volume fraction 21%) to obtain a catalyst.

[0071] The composition of the catalyst obtained according to the above steps is expressed as follows:

[0072] 50%K 0.25 Co 1.5 Ni 5.0 Mg 1.0 Pr 0.6 Fe 3.0 Bi 1.5 Mo 13.6 O x +50%SiO2

[0073] The amount of strong Lewis acid in the catalyst accounts for 57% of the total Lewis acid.

[0074] The activity evaluation of the catalyst showed that the propylene conversion rate of the catalyst was 98.9%, the acrylonitrile selectivity was 84.5%, and the acrylonitrile single-pass yield was 83.6%.

[0075] Example 4 (Compared with Example 1, the mass of the carrier accounts for 40wt% of the total weight of the catalyst)

[0076] 904.2 g (NH4)6Mo7O24 ·4H2O was dissolved in 250mL of water to obtain a mixed solution I. 274.0g of Bi(NO3)3·5H2O, 547.6g of Ni(NO3)2·6H2O, 164.4g of Co(NO3)2·6H2O, 456.4g of Fe(NO3)3·9H2O, 96.6g of Mg(NO3)2·6H2O, 5.3g of KOH, and 98.3g of Pr(NO3)3·6H2O were dissolved in 100mL of water to obtain a mixed solution II. Then, the mixed solution I, the mixed solution II and 2000g of silica sol with a weight concentration of 40wt% were mixed, and 61.4g of oxalic acid was added thereto to obtain a slurry I. Then, the slurry was boiled at 65°C and 300 rpm for 1.5 hours, and then the slurry was transferred to a colloid mill and ground at 750 rpm for 0.5 hours, and then spray-dried at 325°C for 1 hour, with an average diameter of 120 μm, to obtain particles. Finally, the obtained particles were calcined at 600°C for 4 hours in an oxygen-containing atmosphere (oxygen volume fraction 21%) to obtain a catalyst.

[0077] The composition of the catalyst obtained according to the above steps is expressed as follows:

[0078] 60%K 0.25 Co 1.5 Ni 5.0 Mg 1.0 Pr 0.6 Fe 3.0 Bi 1.5 Mo 13.6 O x +40%SiO2

[0079] The amount of strong Lewis acid in the catalyst accounts for 56% of the total Lewis acid.

[0080] The activity evaluation of the catalyst showed that the propylene conversion rate of the catalyst was 98.5%, the acrylonitrile selectivity was 84.3%, and the acrylonitrile single-pass yield was 83.0%.

[0081] Example 5 (Compared with Example 1, Sm replaces Pr)

[0082] 753.4 g (NH4)6Mo7O 24·4H2O was dissolved in 250mL of water to obtain a mixed solution I. 228.3g of Bi(NO3)3·5H2O, 456.2g of Ni(NO3)2·6H2O, 137.0g of Co(NO3)2·6H2O, 380.3g of Fe(NO3)3·9H2O, 80.4g of Mg(NO3)2·6H2O, 4.4g of KOH, and 83.7g of Sm(NO3)3·6H2O were dissolved in 100mL of water to obtain a mixed solution II. Then, the mixed solution I, the mixed solution II and 2500g of silica sol with a weight concentration of 40wt% were mixed, and 51.1g of oxalic acid was added thereto to obtain a slurry I. Then, the slurry was boiled at 65°C and 300 rpm for 1.5 hours, and then the slurry was transferred to a colloid mill and ground at 750 rpm for 0.5 hours, and then spray-dried at 325°C for 1 hour, with an average diameter of 120 μm, to obtain particles. Finally, the obtained particles were calcined at 600°C for 4 hours in an oxygen-containing atmosphere (oxygen volume fraction 21%) to obtain a catalyst.

[0083] The composition of the catalyst obtained according to the above steps is expressed as follows:

[0084] 50%K 0.25 Co 1.5 Ni 5.0 Mg 1.0 Sm 0.6 Fe 3.0 Bi 1.5 Mo 13.6 O x +50%SiO2

[0085] The amount of strong Lewis acid in the catalyst accounts for 55% of the total Lewis acid.

[0086] The activity evaluation of the catalyst showed that the propylene conversion rate of the catalyst was 99.2%, the acrylonitrile selectivity was 85.4%, and the acrylonitrile single-pass yield was 84.7%.

[0087] Example 6 (Compared with Example 1, the contents of Co, Ni and Mg are different)

[0088] 748.7 g (NH4)6Mo7O 24·4H2O was dissolved in 250mL of water to obtain a mixed solution I. 226.9g of Bi(NO3)3·5H2O, 317.4g of Ni(NO3)2·6H2O, 272.2g of Co(NO3)2·6H2O, 377.9g of Fe(NO3)3·9H2O, 119.9g of Mg(NO3)2·6H2O, 4.4g of KOH, and 81.4g of Pr(NO3)3·6H2O were dissolved in 100mL of water to obtain a mixed solution II. Then, the mixed solution I, the mixed solution II and 2500g of silica sol with a weight concentration of 40wt% were mixed, and 50.8g of oxalic acid was added thereto to obtain a slurry I. Then, the slurry was boiled at 65°C and 300 rpm for 1.5 hours, and then the slurry was transferred to a colloid mill and ground at 750 rpm for 0.5 hours, and then spray-dried at 325°C for 1 hour, with an average diameter of 120 μm, to obtain particles. Finally, the obtained particles were calcined at 600°C for 4 hours in an oxygen-containing atmosphere (oxygen volume fraction 21%) to obtain a catalyst.

[0089] The composition of the catalyst obtained according to the above steps is expressed as follows:

[0090] 50%K 0.25 Co 3.0 Ni 3.5 Mg 1.5 Pr 0.6 Fe 3.0 Bi 1.5 Mo 13.6 O x +50%SiO2

[0091] The amount of strong Lewis acid in the catalyst accounts for 54% of the total Lewis acid.

[0092] The activity evaluation of the catalyst showed that the propylene conversion rate of the catalyst was 98.8%, the acrylonitrile selectivity was 84.9%, and the acrylonitrile single-pass yield was 83.9%.

[0093] Example 7 (Compared with Example 1, orthogonal experimental design was used to supplement the implementation of the preferred solution)

[0094] 803.3 g (NH4)6Mo7O 24·4H2O was dissolved in 250mL of water to obtain a mixed solution I. 243.4g of Bi(NO3)3·5H2O, 389.2g of Ni(NO3)2·6H2O, 48.7g of Co(NO3)2·6H2O, 270.3g of Fe(NO3)3·9H2O, 128.7g of Mg(NO3)2·6H2O, 48.7g of RbNO3, and 87.4g of Pr(NO3)3·6H2O were dissolved in 100mL of water to obtain a mixed solution II. Then, the mixed solution I, the mixed solution II, and 2500g of silica sol with a weight concentration of 40wt% were mixed, and 42.5g of glycerol was added thereto to obtain a slurry I. Then, the slurry was boiled at 65°C and 300 rpm for 1.5 hours, and then the slurry was transferred to a colloid mill and ground at 750 rpm for 0.5 hours, and then spray-dried at 325°C for 1 hour, with an average diameter of 120 μm, to obtain particles. Finally, the obtained particles were calcined at 600°C for 4 hours in an oxygen-containing atmosphere (oxygen volume fraction 21%) to obtain a catalyst.

[0095] The composition of the catalyst obtained according to the above steps is expressed as follows:

[0096] 50% Rb 1.0 Co 0.5 Ni 4.0 Mg 1.5 Pr 0.6 Fe 2.0 Bi 1.5 Mo 13.6 O x +50%SiO2

[0097] The amount of strong Lewis acid in the catalyst accounts for 48% of the total Lewis acid.

[0098] The activity evaluation of the catalyst showed that the propylene conversion rate of the catalyst was 99.2%, the acrylonitrile selectivity was 84.6%, and the acrylonitrile single-pass yield was 83.9%.

[0099] Example 8 (Compared with Example 1, orthogonal experimental design was used to supplement the implementation of the preferred solution)

[0100] 601.8 g (NH4)6Mo7O 24·4H2 was dissolved in 250mL of water to obtain a mixed solution I. 121.6g of Bi(NO3)3·5H2O, 255.1g of Ni(NO3)2·6H2O, 182.4g of Co(NO3)2·6H2O, 405.0g of Fe(NO3)3·9H2O, 96.4g of Mg(NO3)2·6H2O, 21.1g of KOH, and 65.4g of Pr(NO3)3·6H2O were dissolved in 100mL of water to obtain a mixed solution II. Then, the mixed solution I, the mixed solution II and 3000g of silica sol with a weight concentration of 40wt% were mixed, and 43.4g of ethylene glycol was added thereto to obtain slurry I. Then, the slurry was boiled at 65°C and 300 rpm for 1.5 hours, and then the slurry was transferred to a colloid mill and ground at 750 rpm for 0.5 hours, and then spray-dried at 325°C for 1 hour, with an average diameter of 120 μm, to obtain particles. Finally, the obtained particles were calcined at 600°C for 4 hours in an oxygen-containing atmosphere (oxygen volume fraction 21%) to obtain a catalyst.

[0101] The composition of the catalyst obtained according to the above steps is expressed as follows:

[0102] 40%K 1.5 Co 2.5 Ni 3.5 Mg 1.5 Pr 0.6 Fe 4.0 Bi 1.0 Mo 13.6 O x +60%SiO2

[0103] The strong Lewis acid content in the catalyst accounts for 43% of the total Lewis acid content.

[0104] The activity evaluation of the catalyst showed that the propylene conversion rate of the catalyst was 99.3%, the acrylonitrile selectivity was 84.5%, and the acrylonitrile single-pass yield was 83.9%.

[0105] Example 9 (Compared with Example 1, orthogonal experimental design was used to supplement the implementation of the preferred solution)

[0106] 895.3 g (NH4)6Mo7O 24·4H2O was dissolved in 250mL of water to obtain a mixed solution I. 271.3g of Bi(NO3)3·5H2O, 433.7g of Ni(NO3)2·6H2O, 162.8g of Co(NO3)2·6H2O, 602.5g of Fe(NO3)3·9H2O, 46.8g of Mn(NO3)2·4H2O, 18.2g of CsNO3, and 97.3g of Pr(NO3)3·6H2O were dissolved in 100mL of water to obtain a mixed solution II. Then, the mixed solution I, the mixed solution II and 2000g of silica sol with a weight concentration of 40wt% were mixed, and 32.1g of oxalic acid was added thereto to obtain a slurry I. Then, the slurry was boiled at 65°C and 300 rpm for 1.5 hours, and then the slurry was transferred to a colloid mill and ground at 750 rpm for 0.5 hours, and then spray-dried at 325°C for 1 hour, with an average diameter of 120 μm, to obtain particles. Finally, the obtained particles were calcined at 600°C for 4 hours in an oxygen-containing atmosphere (oxygen volume fraction 21%) to obtain a catalyst.

[0107] The composition of the catalyst obtained according to the above steps is expressed as follows:

[0108] 60% Cs 0.25 Co 1.5 Ni 4.0 Mn 0.5 Pr 0.6 Fe 4.0 Bi 1.5 Mo 13.6 O x +40%SiO2

[0109] The amount of strong Lewis acid in the catalyst accounts for 54% of the total Lewis acid.

[0110] The activity evaluation of the catalyst showed that the propylene conversion rate of the catalyst was 99.2%, the acrylonitrile selectivity was 84.3%, and the acrylonitrile single-pass yield was 83.6%.

[0111] Example 10 (Compared with Example 1, the added complexing agent is not within the appropriate ratio range)

[0112] 753.5 g (NH4)6Mo7O 24·4H2O was dissolved in 250mL of water to obtain a mixed solution I. 228.3g of Bi(NO3)3·5H2O, 456.3g of Ni(NO3)2·6H2O, 137.0g of Co(NO3)2·6H2O, 380.3g of Fe(NO3)3·9H2O, 80.5g of Mg(NO3)2·6H2O, 4.4g of KOH, and 81.9g of Pr(NO3)3·6H2O were dissolved in 100mL of water to obtain a mixed solution II. Then, the mixed solution I, the mixed solution II and 2500g of silica sol with a weight concentration of 40wt% were mixed, and 255.7g of oxalic acid was added thereto to obtain a slurry I. Then, the slurry was boiled at 65°C and 300 rpm for 1.5 hours, and then the slurry was transferred to a colloid mill and ground at 750 rpm for 0.5 hours, and then spray-dried at 325°C for 1 hour, with an average diameter of 120 μm, to obtain particles. Finally, the obtained particles were calcined at 600°C for 4 hours in an oxygen-containing atmosphere (oxygen volume fraction 21%) to obtain a catalyst.

[0113] The composition of the catalyst obtained according to the above steps is expressed as follows:

[0114] 50%K 0.25 Co 1.5 Ni 5.0 Mg 1.0 Pr 0.6 Fe 3.0 Bi 1.5 Mo 13.6 O x +50%SiO2

[0115] The amount of strong Lewis acid in the catalyst accounts for 63% of the total Lewis acid.

[0116] The activity evaluation of the catalyst showed that the propylene conversion rate of the catalyst was 98.0%, the acrylonitrile selectivity was 83.5%, and the acrylonitrile single-pass yield was 81.8%.

[0117] Example n (Compared with Example 1, the pulp cooking conditions are not within the required range)

[0118] 753.5 g (NH4)6Mo7O 24·4H2O was dissolved in 250mL of water to obtain a mixed solution I. 228.3g of Bi(NO3)3·5H2O, 456.3g of Ni(NO3)2·6H2O, 137.0g of Co(NO3)2·6H2O, 380.3g of Fe(NO3)3·9H2O, 80.5g of Mg(NO3)2·6H2O, 4.4g of KOH, and 81.9g of Pr(NO3)3·6H2O were dissolved in 100mL of water to obtain a mixed solution II. Then, the mixed solution I, the mixed solution II and 2500g of silica sol with a weight concentration of 40wt% were mixed, and 51.1g of oxalic acid was added thereto to obtain a slurry I. Then, the slurry was boiled at 130°C and 300 rpm for 4 hours, and then the slurry was transferred to a colloid mill and ground at 750 rpm for 0.5 hours, and then spray-dried at 325°C for 1 hour, with an average diameter of 120 μm of spray droplets, to obtain particles. Finally, the obtained particles were calcined at 600°C for 4 hours in an oxygen-containing atmosphere (oxygen volume fraction 21%) to obtain a catalyst.

[0119] The composition of the catalyst obtained according to the above steps is expressed as follows:

[0120] 50%K 0.25 Co 1.5 Ni 5.0 Mg 1.0 Pr 0.6 Fe 3.0 Bi 1.5 Mo 13.6 O x +50%SiO2

[0121] The amount of strong Lewis acid in the catalyst accounts for 61% of the total Lewis acid.

[0122] The activity evaluation of the catalyst showed that the propylene conversion rate of the catalyst was 98.3%, the acrylonitrile selectivity was 83.0%, and the acrylonitrile single-pass yield was 81.6%.

[0123] Example 12 (Compared with Example 1, spray drying is not within the required range)

[0124] 753.5 g (NH4)6Mo7O 24·4H2O was dissolved in 250mL of water to obtain a mixed solution I. 228.3g of Bi(NO3)3·5H2O, 456.3g of Ni(NO3)2·6H2O, 137.0g of Co(NO3)2·6H2O, 380.3g of Fe(NO3)3·9H2O, 80.5g of Mg(NO3)2·6H2O, 4.4g of KOH, and 81.9g of Pr(NO3)3·6H2O were dissolved in 100mL of water to obtain a mixed solution II. Then, the mixed solution I, the mixed solution II and 2500g of silica sol with a weight concentration of 40wt% were mixed, and 51.1g of oxalic acid was added thereto to obtain a slurry I. Then, the slurry was boiled at 65°C and 340 rpm for 1.5 hours, and then the slurry was transferred to a colloid mill and ground at 750 rpm for 0.5 hours, and then spray-dried at 340°C for 1 hour, with an average diameter of the spray droplets of 275 μm to obtain particles. Finally, the obtained particles were calcined at 600°C for 4 hours in an oxygen-containing atmosphere (oxygen volume fraction 21%) to obtain a catalyst.

[0125] The composition of the catalyst obtained according to the above steps is expressed as follows:

[0126] 50%K 0.25 Co 1.5 Ni 5.0 Mg 1.0 Pr 0.6 Fe 3.0 Bi 1.5 Mo 13.6 O x +50%SiO2

[0127] The amount of strong Lewis acid in the catalyst accounts for 54% of the total Lewis acid.

[0128] The activity evaluation of the catalyst showed that the propylene conversion rate of the catalyst was 98.2%, the acrylonitrile selectivity was 82.2%, and the acrylonitrile single-pass yield was 80.7%.

[0129] Comparative Example 1 (without using complexing agent)

[0130] 753.5 g (NH4)6Mo7O 24·4H2O was dissolved in 250mL of water to obtain a mixed solution I. 228.3g of Bi(NO3)3·5H2O, 456.3g of Ni(NO3)2·6H2O, 137.0g of Co(NO3)2·6H2O, 380.3g of Fe(NO3)3·9H2O, 80.5g of Mg(NO3)2·6H2O, 4.4g of KOH, and 81.9g of Pr(NO3)3·6H2O were dissolved in 100mL of water to obtain a mixed solution II. Then, the mixed solution I, the mixed solution II and 2500g of silica sol with a weight concentration of 40wt% were mixed to obtain a slurry I. Then, the slurry was boiled at 65°C and 300 rpm for 1.5 hours, and then the slurry was transferred to a colloid mill and ground at 750 rpm for 0.5 hours, and then spray-dried at 325°C for 1 hour, with an average diameter of 120 μm, to obtain particles. Finally, the obtained particles were calcined at 600°C for 4 hours in an oxygen-containing atmosphere (oxygen volume fraction 21%) to obtain a catalyst.

[0131] The composition of the catalyst obtained according to the above steps is expressed as follows:

[0132] 50%K 0.25 Co 1.5 Ni 5.0 Mg 1.0 Pr 0.6 Fe 3.0 Bi 1.5 Mo 13.6 O x +50%SiO2

[0133] The strong Lewis acid content in the catalyst accounts for 67% of the total Lewis acid content.

[0134] The activity evaluation of the catalyst showed that the propylene conversion rate of the catalyst was 97.3%, the acrylonitrile selectivity was 80.3%, and the acrylonitrile single-pass yield was 78.1%.

[0135] Comparative Example 2 (Changing the type of complexing agent)

[0136] 753.5 g (NH4)6Mo7O 24·4H2O was dissolved in 250mL of water to obtain a mixed solution I. 228.3g of Bi(NO3)3·5H2O, 456.3g of Ni(NO3)2·6H2O, 137.0g of Co(NO3)2·6H2O, 380.3g of Fe(NO3)3·9H2O, 80.5g of Mg(NO3)2·6H2O, 4.4g of KOH, and 81.9g of Pr(NO3)3·6H2O were dissolved in 100mL of water to obtain a mixed solution II. Then, the mixed solution I, the mixed solution II and 2500g of silica sol with a weight concentration of 40wt% were mixed, and 34.1g of urea was added thereto to obtain a slurry I. Then, the slurry was boiled at 65°C and 300 rpm for 1.5 hours, and then the slurry was transferred to a colloid mill and ground at 750 rpm for 0.5 hours, and then spray-dried at 325°C for 1 hour, with an average diameter of 120 μm, to obtain particles. Finally, the obtained particles were calcined at 600°C for 4 hours in an oxygen-containing atmosphere (oxygen volume fraction 21%) to obtain a catalyst.

[0137] The composition of the catalyst obtained according to the above steps is expressed as follows:

[0138] 50%K 0.25 Co 1.5 Ni 5.0 Mg 1.0 Pr 0.6 Fe 3.0 Bi 1.5 Mo 13.6 O x +50%SiO2

[0139] The amount of strong Lewis acid in the catalyst accounts for 63% of the total Lewis acid.

[0140] The activity evaluation of the catalyst showed that the propylene conversion rate of the catalyst was 96.8%, the acrylonitrile selectivity was 79.5%, and the acrylonitrile single-pass yield was 77.0%.

[0141] Table 1 Catalyst composition and properties of each example

[0142]

[0143] Table 2 Catalyst activity evaluation results for each case

[0144]

[0145] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A catalyst for preparing acrylonitrile by ammoxidation of propylene, characterized in that: The catalyst comprises an active component and a carrier, wherein the strong Lewis acid content in the catalyst does not exceed 60% of the total Lewis acid content, preferably 30% to 60%.

2. The catalyst according to claim 1, characterized in that The active component is a composite oxide, which includes at least oxides of three elements: Fe, Mo, and Bi; preferably, its general formula is A a B b C c Fe d Bi e Mo f O x , wherein A is selected from alkali metal elements, preferably at least one of Li, Na, K, Rb and Cs; B is selected from at least one of Ca, Ba, Sr, Mn, Co, Ni, Zn, Mg, Al, Cr, Nb, Sb, Te and W; C is selected from at least one of rare earth elements, preferably at least one of La, Ce, Pr, Nd and Sm.

3. The catalyst according to claim 2, characterized in that The value range of a is 0 to 3, preferably 0.05 to 2.5; the value range of b is 0 to 15, preferably 1 to 12.5; the value range of c is 0 to 5, preferably 0.01 to 3; the value range of d is 0.1 to 12, preferably 0.5 to 10; the value range of e is 0.01 to 5, preferably 0.01 to 3; the value range of f is 9 to 16, preferably 10 to 15; x is the total number of oxygen atoms required to satisfy the valence of each element in the above-mentioned active components.

4. The catalyst according to claim 1, characterized in that The carrier is selected from at least one of silicon dioxide, zirconium dioxide and titanium dioxide, and silicon dioxide is more preferred.

5. The catalyst according to claim 2 or 3, characterized in that In the active component, the atomic molar ratio of e / f is 0.005 to 0.35, preferably 0.01 to 0.25; the atomic molar ratio of d / f is 0.02 to 1.25, preferably 0.1 to 0.

8.

6. The catalyst according to claim 1, characterized in that Based on the weight of the catalyst, the content of active components in the form of composite oxides is 30% to 80%, and the content of the carrier is 20% to 70%.

7. A method for preparing a catalyst according to any one of claims 1 to 6, comprising the following steps: (a) dissolving a Mo precursor to obtain a mixed solution I; (b) dissolving an Fe precursor, a Bi precursor, an optional precursor of an A element, an optional precursor of an B element, and an optional precursor of an C element to obtain a mixed solution II; (c) mixing the complexing agent with the mixed solution I obtained in step (a), the mixed solution II obtained in step (b), and the carrier precursor solution to obtain slurry I; (d) boiling the slurry I obtained in step (c) to obtain slurry I'; (e) The slurry I' obtained in step (d) is transferred to a colloid mill for grinding, spray-drying and calcining to obtain the catalyst for preparing acrylonitrile by ammoxidation of propylene.

8. The method for preparing the catalyst according to claim 7, characterized in that: The molar ratio of the complexing agent contained in the slurry I in step (c) to the total molar number of Fe, Bi and Mo contained in the active component precursor is 0.01-0.25:

1.

9. The method for preparing the catalyst according to claim 7, characterized in that: In step (c), the complexing agent is selected from any one of oxalic acid, citric acid, tartaric acid, ethylenediaminetetraacetic acid, ethylene glycol, and glycerol.

10. The method for preparing the catalyst according to claim 7, characterized in that: In step (c), the carrier precursor is a silicon dioxide, zirconium dioxide, or titanium dioxide precursor, preferably a silica sol.

11. The method for preparing the catalyst according to claim 10, characterized in that: The solid content of the silica sol is 20-50 wt % in terms of silicon dioxide, and the average particle size is 5-40 nm.

12. The preparation method according to claim 7, characterized in that: In step (d), the conditions for cooking the pulp include: a temperature of 10 to 80° C., a time of 0.1 to 12 h, and a stirring speed of 200 to 1000 rpm; and / or, In step (e), the grinding conditions include: a rotation speed of 500 to 1500 rpm and a time of 0.5 to 1.5 h; and / or, In step (e), the spray drying conditions include: the drying heat source is air, the drying temperature is 250-400° C., the drying time is 0.5-3 hours, and the average diameter of the spray droplets is 40-200 μm; and / or, In step (e), the calcination conditions include: in an oxygen-containing atmosphere, a calcination temperature of 200 to 750° C., and a calcination time of 2 to 8 hours.

13. Use of the catalyst according to any one of claims 1 to 6 in the preparation of acrylonitrile by ammoxidation of propylene.

Citation Information

Patent Citations

  • Production technology of nicotinic acid

    CN106381318A

  • N-butane dehydrogenation catalyst and preparation method thereof

    CN112717920A

  • Ammonia oxidation catalyst as well as preparation method and application thereof

    CN115487820A